Ethical Considerations for Postdisaster Fieldwork and Data Collection in the Caribbean. (July 2020) - Louis-Charles, Hans M.; Howard, Rosalyn; Remy, Lionel; Nibbs, Farah; Turner, Grace
The postdisaster environment presents a multitude of ethical and logistical challenges for researchers interested in gathering timely and unpreserved data. Due to the unavailability of secondary data in the immediate aftermath of disasters, postdisaster researchers have become dependent on qualitative methods that involve engaging with disaster survivors as research participants. This is a common interaction in the Caribbean due to the region's high occurrence of disasters and human participant engagement by external researchers during the postdisaster phase. However, due to escalating unethical practices since the 2010 Haiti earthquake, Caribbean nations are beginning the process of censuring unapproved postdisaster fieldwork by external researchers. In this study, the authors approach these ethical considerations through a justice lens to propose a checklist for postdisaster researchers interested in ethical fieldwork and justice for their research participants. Correspondence with Caribbean emergency managers confirms the negative perception toward external researchers and the trend of enacting protocols that stop unvetted community access following disasters. However, these local agencies acknowledge the benefits of ethical postdisaster research and are open to serving as research coordinating centers. Such coordinating centers would harness local capabilities and lower the likelihood of the duplication of research topics and the overburdening of survivors as research participants.